PENGARUH BERAT DAN LAMA WAKTU PENYEDUHAN TERHADAP KADAR KAFEIN TEH - Ririn Yuningsih; Samingan Samingan; Muhibbuddin Muhibbuddin (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2012)
Tea is the most consumed beverage after water and touted as a beverage rich in benefits. In addition to the benefits of tea, there are also substances contained in tea that result in less good for the body, the substance is caffeine. Amount of caffeine depending on the spesies, processing and brewing method. The research "Influence of Weight and Time Brewing on the Tea Caffeine " has been done since May to September 2012 at the Laboratory of Chemical FMIPA Unsyiah. The purpose of the research were to know the weight and time brewing on tea caffeine, and to know the weight and length of the maximum brewingon tea caffeine. The method used experimental design with Completely Randomized Design (CRD) 3 x 3 factorial pattern with three times replication. Two factors examined were heavy tea and tea brewing time. The weight was three level (tea weight 1 g, 2 g, and 3 g) and length of brewing also consists of three level (3 minutes, 6 minutes, and 9 minutes). Data was analyzed by ANOVA test followed by Duncan test. The results show that heavy tea was significant effect on the rate of caffeine, while time brewing was not significant. Similarly, the interaction between heavy with tea brewing time was not significant. The maximum weight and length of brewing were 3 grams and 9 minutes, which is 29,3214 mg (w/w).